2011
DOI: 10.1021/jo201567d
|View full text |Cite
|
Sign up to set email alerts
|

Concerted vs Stepwise Mechanisms in Dehydro-Diels–Alder Reactions

Abstract: The Diels-Alder reaction is not limited to 1,3-dienes. Many cycloadditions of enynes and a smaller number of examples with 1,3-diynes have been reported. These "dehydro"-Diels-Alder cycloadditions are one class of dehydropericyclic reactions which have long been used to generate strained cyclic allenes and other novel structures. CCSD(T)//M05-2X computational results are reported for the cycloadditions of vinylacetylene and butadiyne with ethylene and acetylene. Both concerted and stepwise diradical routes hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
65
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 86 publications
10
65
1
Order By: Relevance
“…A considerable amount of experiments and theoretical studies have shown that the activation energy for both mechanisms is nearly similar, and it is the nature of the molecule itself, or the substituents presents in the substrate, that may encourage one reaction path over the other [1][2][3][4][5][6][7][8]. Conversely, the story of the reverse process is quite different.…”
Section: Introductionmentioning
confidence: 99%
“…A considerable amount of experiments and theoretical studies have shown that the activation energy for both mechanisms is nearly similar, and it is the nature of the molecule itself, or the substituents presents in the substrate, that may encourage one reaction path over the other [1][2][3][4][5][6][7][8]. Conversely, the story of the reverse process is quite different.…”
Section: Introductionmentioning
confidence: 99%
“…50 kcal mol −1 (Δ) 1 (cf. ΔE rxn = −51.4 kcal mol −1 for the parent ethyne + 1,3-butadiyne to benzyne 4 ); (ii) this thermal mode of benzyne generation is complementary to all previously reported, preparatively practical methods in two important ways—the triyne precursors are not, themselves, benzene derivatives and the aryne is formed in the absence of reagents (e.g., bases or reducing agents) and byproducts (e.g., metal salts, amines, or halide ions) that can affect or, in some instances, interfere with the benzyne trapping reactions; and (iii) a beneficial consequence of point (ii) is that inherent reactivity of benzynes can sometimes be probed more fundamentally and/or that new types of aryne trapping reactions can be uncovered. 5,6 An example of this latter feature is the net addition of a silyl ether (like that in 1 ) across the pair of strained benzyne sp-hybridized carbons to give an o -(trialkylsilyl)aryl ether moiety (like that in 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…50 kcal•mol −1 more stable than the triyne precursor (! ), 14, 7 yet this intermediate, albeit aromatic, is rendered quite reactive because of its large strain energy (ca. 54 kcal•mol −1 15 ).…”
Section: Introductionmentioning
confidence: 99%